Near-field optical microscopy toward its applications for biological studies - Takayuki Umakoshi (Biophysics and Physicobiology, 2023)
Near-field scanning optical microscopy (NSOM) is a super-resolution optical microscopy based on nanometrically small near-field light at a metallic tip. It can be combined with various types of optical measurement techniques, including Raman spectroscopy, infrared absorption spectroscopy, and photoluminescence measurements, which provides unique analytical capabilities to a variety of scientific fields. In particular, to understand nanoscale details of advance materials and physical phenomena, NSOM has been often adopted in the fields of material science and physical chemistry. However, owing to the recent critical developments showing the great potential for biological studies, NSOM has also recently gained much attention in the biological field. In this article, we introduce recent developments made in NSOM, aiming at biological applications. The drastic improvement in the imaging speed has shown a promising application of NSOM for super-resolution optical observation of biological dynamics. Furthermore, stable imaging and broadband imaging were made possible owing to the advanced technologies, which provide a unique imaging method to the biological field. As NSOM has not been well exploited in biological studies to date, several rooms need to be explored to determine its distinct advantages. We discuss the possibility and perspective of NSOM for biological applications. This review article is an extended version of the Japanese article, Development of Near-field Scanning Optical Microscopy toward Its Application for Biological Studies, published in SEIBUTSU BUTSURI Vol. 62, p. 128–130 (2022).